Estabelecimento de metodologia para determinação de 93Zr em rejeitos radioativos por espectrometria de cintilação liquida (LSC) e espectrometria de massa com plasma indutivamente acoplado (ICP-MS) - Thiago Cesar de Oliveira (2014)
The zirconium-93 is a long-lived pure -particle-emitting radionuclide produced from 235U fission and from neutron activation of the stable isotope 92Zr and thus occurring as one of the radionuclides found in nuclear reactors. Due to its long half life, 93Zr is one of the radionuclides of interest for the performance of assessment studies of waste storage or disposal. Measurement of 93Zr is difficult owing to its trace level concentration and its low activity in nuclear wastes and further because its certified standards are not frequently available. The aim of this work was to develop a selective radiochemical separation methodology for the determination of 93Zr in nuclear waste and analyze it by Liquid Scintillation Counting (LSC) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). To set up the radiochemical separation procedure for zirconium, a tracer solution of 95Zr and its 724 keV -ray measurements by - spectrometry were used in order to follow the behavior of zirconium during the radiochemical separation. For the LSC technique a 55Fe solution, which is one of the major interfering measures zirconium, was used to verify the decontamination factor during the separation process. The efficiency detection for 63Ni was used to determination of 93Zr activity in the matrices analyzed. The limit of detection of the 0.05 Bq l1 was obtained for 63Ni standard solutions by using a sample:cocktail ratio of 3:17 mL for Optiphase Hisafe 3 cocktail. For the ICP-MS technique a zirconium stable solution was used to verify the zirconium behavior and recovery during radiochemical separation and a solution of Ba, Co, Eu, Fe, Mn, Nb, Sr and Y was used to verify the decontamination factor during the separation process. A standard solution 93Nb as isotope for determining the 93Zr by ICP-MS was used for calibration and analysis. The detection limit of 0.039 ppb was obtained for the standard solution of zirconium. Then, the protocol was applied to low level waste (LLW) and intermediate level waste (ILW) from nuclear power plants.